Research on the mechanical properties and microstructure of fly ash-based geopolymers modified by molybdenum tailings. (3rd July 2023) - Zhang, Jinrui; Fu, Yin; Wang, An; Dong, Biqin
Highlights: Under a fixed liquid to solid ratio, the addition of MT can retard the setting of the pastes as well as improve the fluidity of them. The addition of MT can cause the increase of drying shrinkage of fly ash-based geopolymer due to the increase of capillary pore volume fraction. MT can be dissolved in alkaline activator to form nanorods filling the pore structure of fly ash based-geopolymers and reducing the damage of microstructure. Abstract: The environmental and economic problems caused by the accumulation of molybdenum tailings (MT) have become increasingly prominent. Therefore, a cost-effective method is urgently needed to realize the resource utilization of MT. In this paper, the mechanism of action of MT on fly ash-based geopolymers were systematically researched. The effects of MT on the macro-properties of fly ash-based geopolymers were researched in terms of fluidity, setting time, drying shrinkage and mechanical strength. The reaction mechanism of fly ash-based geopolymers modified by MT were analyzed from the perspective of microstructure and micromorphology by using scanning electron microscopy (SEM), energy dispersive spectroscopy (EDS), X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), thermogravimetric (TG) and nitrogen adsorption/desorption (NAD) methods. The results show that the addition of MT could effectively improve the fluidity of fly ash-based geopolymer paste, appropriately delay its setting time and increase its drying shrinkage; When the content of MT was 20%, the bending strength of fly ash-based geopolymers were significantly improved, and the flexural strength at 3, 7 and 28 days were increased by 79.2%, 47.4% and 19% respectively. The SEM, FTIR and TG results confirmed that the main product was glassy sodium calcium aluminum silicate hydrate (N(C)-A-S-H) gel, which was used as a binder to connect residual raw material particles and form hardened geopolymer materials. The XRD results show that the addition of MT would not lead to the formation of new crystal phases in the fly ash-based geopolymers, and when the addition of MT was 20%, the diffraction peak intensity of the crystal phase structure of the fly ash-based geopolymers basically were not changed obviously. The NAD results show that the addition of 20% MT could significantly improve the pore structure of fly ash-based polymers, increased the volume fraction of micropores, and reduced the volume fraction of macropores. The SEM/EDS results show that the MT could be dissolved in alkali activator to form nanorods to fill the pore structure of fly ash-based geopolymers, thus reducing the cracks and defects of fly ash-based geopolymers and improving the compactness of the microstructure.